Computational fluid dynamic model for smoke control of building basement. (June 2023) - Nguyen, Tue Duy; Bui, Ha Manh
Abstract: Fire accidents cause damage and injuries; hence, fire protection is imperative for building construction. Smoke control reduces smoke concentrations as well as the temperature to enable evacuation of building residents. Moreover, firefighters easily extinguish fire with low smoke concentrations and temperatures. In this study, the Fire Research Station, UK standard, was applied to calculate the flow rate of the smoke exhaust fan for a basement with dimensions of 30 m × 20 m × 4 m using a computational fluid dynamic (CFD) code in the transient mode. The model was established by Revit 2020, and the fire simulation was conducted using Autodesk CFD 2020. The fire simulation was analyzed under the total exhaust fan volume values of 20000 m 3 /h, 50000 m 3 /h and 100000 m 3 /h, the air change per hour (ACH) values equivalent to 8.5, 21 and 42.5, respectively. The results reveal that the total exhaust fan volume of 100000 m 3 /h is optimum because at 1200 s, after the fire, the temperature of the basement is less than 1.4 m is less than 65 °C, and smoke visibility is ∼10 m. Moreover, the amount of smoke escaping through the doors was the lowest. This condition is suitable for evacuation and for firefighters to put out the fire. In addition, a volume of 100000 m 3 /h was compatible with the formula of the standard. Therefore, Autodesk CFD is also an optimum choice for engineers to verify their design before conducting site work to save time and increase confidence.